PREVALENCE AND RISK FACTORS FOR HEPATITIS C AND HUMAN IMMUNODEFICIENCY VIRUS CO-INFECTION AMONG CHILDREN IN ENUGU, NIGERIA - Eze, Jude Chijioke; Ibeziako, Ngozi S.; Ikefuna, Anthony N; Nwokoye, Ikenna C; Uleanya, Nwachinaemere D; Ilechukwu, Gideon C (African Journal of Infectious Diseases (AJID), 2013)
Background: Hepatitis C virus (HCV) and Human Immunodeficiency virus (HIV), are major public health challenges in the developing world especially sub-Saharan Africa. The aim of this study was to determine the prevalence and risk factors of Hepatitis C virus infection among children infected with HIV.Methods: This was a cross-sectional study conducted at the Paediatric HIV Clinic, UNTH, Enugu between July and December 2009. Antibodies to HCV were analyzed by newer generation rapid chromatographic immunoassay method using the Chromatest one step HCV test kit. The data was analysed using the Statistical Package for Social Sciences (SPSS) version 15 statistical software. The chi squared test was used to test for significant association of categorical variables. A p-value of <0.05 was accepted as significant.Results: One hundred and eighteen children HIV-infected children, aged between eighteen months to fifteen years were included in the data analysis. Eight of the HIV infected subjects were positive for HCV, giving an HIV-HCV co-infection prevalence of 6.8%. Co-infection was more prevalent among males and in those in age group 11-15 years. Blood transfusion, irrespective of frequency (p<0.015), and injections for immunization (p<0.049) were the significant risk factors noted Conclusion: There is need for strengthening of existing preventive strategies against HCV and HIV infections such as screening of donor blood and safe injection practices in our locality.